Solve the equation. Check each solution by substituting it back into the original equation before submitting your quick check.

(g + 4) – 3g = 1 + g
(1 point)
Responses

g = 1
g = 1

g = 4
g = 4

no solution
no solution

identity

1 answer

g = 1
Checking:
(1 + 4) - 3(1) = 5 - 3 = 2 which is not equal to 1 + 1 = 2.
Therefore, g = 1 is not a solution to the equation.

g = 4
Checking:
(4 + 4) - 3(4) = 8 - 12 = -4 which is not equal to 1 + 4 = 5.
Therefore, g = 4 is not a solution to the equation.

There is no solution to the equation.